Sustainability and Development in Asia and the Pacific: Emerging Policy Issues - Guo, Xiumei; Marinova, Dora (World Scientific, 2018)
The UN Sustainable Development Goals provide a common global agenda for development. However, the emerging policy issues vary greatly across the world.